Determinant of Enterprise Risk Management Disclosure with the Board of Commissioners as a Moderating Variable - Retnoningrum Hidayah; Suntari; Trisni Suryarini; Sara R Basher; Anwar Zahid (Jurnal Dinamika Manajemen, 2026)
This study examines the effect of the independent board of commissioners and managerial ownership on enterprise risk management (ERM) disclosure. Furthermore, this study uses the board of commissioners as a moderating variable. The sample uses financial sector companies listed on the Indonesia Stock Exchange during the 2020-2023 period. This study uses a purposive sampling technique. The findings reveal that an independent board of commissioners and managerial ownership positively influence enterprise risk management (ERM) disclosure. The board of commissioners can strengthen the effect of managerial ownership on enterprise risk management disclosure. The novelty of this research lies in incorporating board size as a moderating variable in the context of ERM disclosure. Hence, this study offers new insights into the nexus between governance and risk management. This study also contributes to ERM literature by emphasizing the contingent role of board characteristics in shaping risk disclosure practices. Nevertheless, this study only focuses on financial companies. Therefore, future research should include broader industry coverage and adopt longer observation periods to enhance the generalizability and robustness of the results.